Return to whispering pines [large type] - Dunn, Scarlett (Dunn, Scarlett. Langtry sisters trilogy., 2019)
"Adelaide Langtry may not be as beautiful as her sisters, but she has determination to spare. She'll need it if she's to succeed as a schoolteacher in her old hometown and care for the three abandoned siblings she brought from Boston. In Whispering Pines, Addie hopes to establish an orphanage, but she must also contend with her past, including her outlaw brother, Frank. Orphaned as a boy, Sheriff Jack Roper understands the turmoil faced by Addie's young charges. Though he tells himself he has all the responsibility he needs, the handsome lawman is quickly charmed by the children and by the spirited, generous woman intent on helping them. Still, he has his own duty - to capture Frank Langtry and bring him to justice. This is part of "The Landry Sisters" series."--